A interferência da jornada de trabalho na qualidade do serviço: contribuição à gestão de pessoas - Silva, Luis Carlos de Paula e; Juliani, Carmen Maria Casquel Monti [UNESP] (My University, 2012)
The hours of working for the professionals of the health and mainly for the nursing has constituted one of the factors that come fomenting the quarrel concerning its interference in the results and the quality of the given services, in reason of being exhausting. The objective was to compare the hospital pointers in two distinct periods: one, with hours of working of the nursing of 6 hours and another one, with 12 hours. Quantitative, analytical, retrospective and comparative study was performed. It was shown that the pointers of fall, number of deaths and average of hospital permanence had presented lower indices in the period where the institution adopted the day of 6 hours; and, when it adopted the day of 12 hours, had a growth of 126% in the number of falls and 27.6% in the deaths. Long hours of working for the nursing intervenes with the results of some hospital pointers, for reflecting directly in the quality of the care to the user and in the security of the worker.

A jornada de trabalho para os profissionais da saúde e, principalmente, para a enfermagem tem constituído um dos fatores que vêm fomentando a discussão acerca de sua interferência nos resultados e na qualidade dos serviços prestados, em razão de ser exaustiva. O objetivo foi comparar os indicadores hospitalares em dois períodos distintos: um, com jornada de trabalho da enfermagem de 6 horas, e outro, com 12 horas. Foi realizado estudo quantitativo, analítico, retrospectivo e comparativo. Demonstrou-se que os indicadores de queda, número de óbitos e média de permanência hospitalar apresentaram índices mais baixos no período em que a instituição adotava a jornada de 6 horas; e, quando adotava a jornada de 12 horas, houve um crescimento de 126% no número de quedas e 27,6% nos óbitos. Jornadas de trabalho longas para a enfermagem interferem nos resultados de alguns indicadores hospitalares, por refletirem diretamente na qualidade do cuidado ao usuário e na segurança do trabalhador.
Interference of the day working on the quality of service: contribution to the people management
Keywords: Nursing; Work hours; Indicators; Health personnel management; Enfermagem; Jornada de trabalho; Indicadores; Administração de recursos humanos em saúde